PERBEDAAN PENGGUNAAN METODE DEMONSTRATION DAN METODE ROLE PLAYING TERHADAP HASIL BELAJAR SPIKE BOLAVOLI (STUDI PADA SISWA KELAS XI IPS-1 DAN IPA-1 MAN 6 JOMBANG) - DWI SETYOROSADI, DEVIT (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract In learning activities students will feel bored when learning is not as expected of students . Therefore , the most strategic activities in the teaching-learning process is the selection of the method of learning before learning process begin . Students with effective learning will be easier to capture learning materials and perform the given task motion so the goal of learning can be achieved with either . The purpose of this study is to determine how much difference the use methods of demonstration and methides of role playing in learning volleyball spike in class XI . This research is quasi- experimental research design with One Group Pretest – Posttest Design . The population in this study were students of class XI islamic senior high school 6 Jombang which consists of 1 class IPA and 3 -class IPSand all amount are 113 students . Samples taken are students ofclass XI IPS - 1 as a group demonstrationas much as 25 students  IPA - 1 as a group of role playing as much as 25 students islamic senior high school 6 Jombang by purposive sampling . From the results of this study similar results of different test samples ( pretest - posttest ) showed that for the group of demonstration results at 7.15 t greater than t table 1.711 , so the difference between pretest and posttest results demonstrationwith group increased by 23.22 % , while the role playing group t count of 3.30 results greater than 1,711 t table , so that the difference between pretest and posttest results role playing group with an increase of 12.06 % , respectively - each with a 5 % error level then the hypothesis is accepted . Volleyball spike learning outcomes based on different test different samples showed that t of 5.29 is greater than t table 2.021 with standard error of 5 %, then the hypothesis is accepted so that we can conclude the existence of differences in the use of the method of demonstration and role playing methods on learning outcomes of students volleyball spike class XI and IPS - 1 - 1 IPA islamic senior high school 6 Jombang . Keywords:  Method Demonstration, Role Playing Methods, Spike volleyball and Learning Outcomes.